ARCHITECTURE OF SMART TOURISM APPLICATION: A DEVELOPING COUNTRIES’ PERSPECTIVE A CASE STUDY IN INDONESIA - Meiyanti, Ruci; Jumaryadi, Yuwan; Fajriah, Riri; Priambodo, Bagus (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2024)
Beautiful, comfortable, safe, and affordable tourist attractions are every tourist’s dream. Meanwhile, tourism in developing countries, the authenticity and uniqueness of nature and culture are the main attractions for tourists. The lack of accurate information that can accommodate tourist locations, local culture, unique tourism, transportation, and accommodation of a tourist attraction for developing countries is an obstacle to the success of tourist visits. The role of technology and society can help the concept of smart tourism governance for developing countries. Therefore, a framework model is needed that can explore the advantages of tourism in developing countries. The success of Smart Tourism cannot be separated from the development of the application architecture that is used as the basis for developing the Smart Tourism system application. So, the purpose of this study is to create an informative, accurate, safe, and easy smart tourism application architecture. This study uses a qualitative method, namely with literature studies and in-depth interviews were also conducted with tourism and informatics experts. The Mc Farlan Matrix used in the Ward and Peppard method and the TOGAF framework are used in the formation of smart tourism applications. The results of this study are The results of this study are in the form of an application architecture that focuses on stakeholder interests in the form of Smart Tourism Service Application Architecture for various Stakeholders which is an integration of smart tourism organization, smart destination, smart service, smart decision, smart share, smart experience, smart recommendation.